TRAINING OF FUTURE PRIMARY SCHOOL TEACHERS TO TEACH PREPARATORY COURSE OF COMPUTER SCIENCE - Kozak, Т.М. (Journal of Information Technologies in Education (ITE), 2016)
The introduction of preparatory course of computer science in primary school led to the introduction in the educational process of higher pedagogical educational institution disciplines that form informatics and methodical skills of future primary school teachers. It is therefore important to develop a methodology to ensure the proper level for the students specialty "Primary education": programs relevant courses, lectures, laboratory works, recommendations for practical (seminar) classes and individual work of future specialists and so on. Article is devoted features training of primary school teachers to teach course of computer science in Ivan Franko Drohobych State Pedagogical University. In particular, specify the purpose and objectives of the course "Information with methods of teaching in primary school," analyzes the content of lectures, laboratory works, some aspects of individual work of students and skills that future professionals must master.